Simplify (2n + 5) - (3n + 7) + (4n - 9).

Question

Asked 9/19/2014 11:15:00 AM

Updated 9/19/2014 12:46:28 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [9/19/2014 12:46:27 PM], Confirmed by andrewpallarca [9/19/2014 12:46:29 PM]

s

= 2n + 5 - 3n - 7 + 4n - 9

= (2n - 3n + 4n) + (5 - 7 - 9)

= 3n + - 11

bananayumboat|Points 590|

= -4 + 8 + 2 + 3x - 3x + 2x^2 - 5x^2;

= -3x^2 + 6

Q - [R + S]

= (3x^2 + 5x - 2) - [(2 - x^2) + (2x + 5)]

= (3x^2 + 5x - 2) - (2 - x^2 + 2x + 5)

= (3x^2 + 5x - 2) - (7 - x^2 + 2x)

= 3x^2 + 5x - 2 - 7 + x^2 - 2x

= 4x^2 + 3x - 9

= -3p^3 + 5p - 2p^2 - 4 - 12p + 5 + 8p^3

= (-3p^3 + 8p^3) - 2p^2 + (5p - 12p) + (-4 + 5)

= 5p^3 - 2p^2 - 7p + 1

= a - [b - (c - d + e - f) - g]

= a - (b - c + d - e + f - g)

= a - b + c - d + e - f + g

Question

Asked 9/19/2014 11:15:00 AM

Updated 9/19/2014 12:46:28 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [9/19/2014 12:46:27 PM], Confirmed by andrewpallarca [9/19/2014 12:46:29 PM]

Rating

There are no new answers.

Factor 6x^2 - 17x + 5 **Weegy:** 6x^2 - 17x + 5 = (3x - 1)(2x - 5) **User:** Find the greatest common factor of 15x^2y^3 and -18x^3yz **Weegy:** The greatest common factor of 15x^2y^3 and -18x^3yz is 3x^2y. **User:** How many terms are in the polynomial abcd + e - fg + h^2? **Weegy:**
The polynomial abcd + e - fg + h^2 has FOUR terms.
**User:** Factor 3x^2 - 15x - 42. **Weegy:**
3x^2 - 15x - 42 = 3(x + 2)(x - 7)
**User:** Simplify m - {n + [p - (m + n - p)]}. **Weegy:** m - {n - [p + (m + n - p)]} = m - [n - (p + m + n - p)] = m - [n - (m + n)] = m - (n - m - n) = m - (-m) = m + m = 2m **User:** Find the quotient.
(6x^2 - x - 40) ÷ (5 + 2x) **Weegy:**
(6x^2 - x - 40) ÷ (5 + 2x) = 3x - 8
**User:** Divide x^4 + 7 by x - 3. **Weegy:** (x^4 + 7) ÷ (x - 3) = x^3 + 3x^2 + 9x + 27 R. 88
to check:
(x^3 + 3x^2 + 9x + 27)(x - 3)
= x^4 - 81 + 88
= x^4 - 7 **User:** Choose the product.
a^3b^2 · 4ab^3 (More)

Question

Not Answered

Updated 9/25/2014 2:38:56 PM

1 Answer/Comment

a^3b^2 · 4ab^3 = 4a^4b^5

Added 9/25/2014 2:38:56 PM

This answer has been confirmed as correct and helpful.

Factor the four-term polynomial.
pq - 3r + pr - 3q **Weegy:** pq - 3r + pr - 3q = (p - 3)(q + r) **User:** Choose the product.
(5x^2 + 2x - 3)(x - 1) **User:** Factor 360t + 10t^3 - 120t^2. **Weegy:** 360t + 10t^3 - 120t^2 = 10t(t - 6)(t + 6) = 10t(t - 6)^2 **User:** Factor -2bk^2 + 6bk - 2b. **Weegy:** -2bk^2 + 6bk - 2b = -2b(k^2 - 3k + 1) **User:** Simplify the expression.
2(3y - 7) - 5y(2 - y) **Weegy:** 2(3y - 7) - 5y(2 - y) = 6y - 14 - 10y + 5y^2 = 5y^2 - 4y - 14 **User:** Factor the following polynomial completely.
-x^2y^2 + x^4 + 9y^2 - 9x^2 **Weegy:** -x^2 y^2 + x^4 + 9y^2 - 9x^2 = -x^2(y^2 - x^2) + 9(y^2 - x^2) = (y^2 - x^2)(-x^2 + 9) = (y + x)(y - x)(3 + x)(3 - x) = (x + 3)(x - 3)(x + y)(x - y) **User:** Select the correct difference.
5d^2 + 4d - 3 less 2d^2 - 3d + 4 **Weegy:**
(5d^2 + 4d - 3) - (2d^2 - 3d + 4)
= (5d^2 + 4d - 3) + (-2d^2 + 3d - 4)
= 3d^2 + 7d - 7
**User:** Choose the product.
a^3b^2 · 4ab^3 **Weegy:** a^3b^2 * 4ab^3 = 4a^4b^5 **User:** Factor completely.
x^3 + 6x^2 - 4x - 24 **Weegy:** x^3 + 6x^2 - 4x - 24 = x^2(x + 6) - 4(x + 6) = (x + 6)(x^2 - 4) = (x + 6)(x + 2)(x - 2) **User:** Factor completely.
2ay^2 + 5ay - 3a **Weegy:** 2ay^2 + 5ay - 3a = a(2y^2 + 5y - 3) = a(y + 3)(2y - 1) **User:** Factor completely.
n^2 + 7n - 44 **Weegy:** n^2 + 7n - 44 = (n + 11)(n - 4) **User:** Factor completely.
49t 6 - 4k 8 **Weegy:** 49t^6 - 4k^8 = (7t^3 - 2k^4)(7t^3 + 2k^4) **User:** Factor completely.
-2k - k^3 - 3k^2 **Weegy:** -2k - k^3 - 3k^2 = -k(2 + k^2 + 3k) = -k(k^2 + 3k + 2) = -k(k +1)(k +2) **User:** Factor completely.
a^2 + 28a + 27 **Weegy:** a^2 + 28a + 27 = (a + 1) (a + 27)
**User:** Factor completely.
5x^2 + 10x - 40 **Weegy:** 5x^2 + 10x - 40 = 5(x^2 + 2x - 8) = 5(x + 4)(x - 2) **User:** Find the greatest common factor of 8a^3b^2 and 12ab^4 **Weegy:** The greatest common factor of 8a^3b^2 and 12ab^4 is 4ab^2. (More)

Question

Updated 9/25/2014 2:32:26 PM

1 Answer/Comment

(5x^2 + 2x - 3)(x - 1)

= 5x^3 + 2x^2 - 5x^2 - 3x - 2x + 3

= 5x^3 - 3x^2 - 5x + 3

= 5x^3 + 2x^2 - 5x^2 - 3x - 2x + 3

= 5x^3 - 3x^2 - 5x + 3

Added 9/25/2014 2:32:26 PM

This answer has been confirmed as correct and helpful.

32,762,238

questions answered

There are no comments.